Occurrence of endoparasites in creole goats under an extensive production system on the southern coast of Peru - Sessarego Davila, Emmanuel Alexander; Soca Jorge, Jhony; Terán Rojas, Jose Alfonso; Dávalos Almeyda, María Emilia; Valdivia Zevallos, Justo; Ruiz Chamorro, Jose Antonio; Cruz Luis, Juancarlos Alejandro; Cruz Flores, Danny Julio (MDPI, 2025)
Endoparasitosis is a critical health challenge in the management of Creole goats under extensive production systems due to its negative impact on animal health and productivity. This study determined the occurrence of endoparasites and identified associated risk factors in Creole goats from the southern coast of Peru. Fecal samples were collected from 129 goats in two localities of the Pisco province to detect the presence of oocysts from Eimeria spp. and eggs from trichostrongyles, Skrjabinema spp., Trichuris spp., and Fasciola hepatica. Data were analyzed using logistic regression models and adjusted through bootstrapping and stepwise selection methods, with locality, feeding type, age, and body condition as predictive variables. The results revealed a high occurrence of Eimeria spp. (86.0%) and trichostrongyles (65.1%), while Fasciola hepatica (14.0%) and Skrjabinemaspp. (7.0%) were exclusively identified in Independencia and San Clemente, respectively. Mixed infestations were predominant (65.9%), occurring more frequently in Independencia (75.9%) than in San Clemente (57.7%) (OR: 2.26, p < 0.05). The likelihood of infestation was significantly higher in Independencia for Eimeria spp. (OR: 5.72, p < 0.01) and Fasciola hepatica (OR: 61.4, p < 0.01). Moreover, goats fed exclusively on alfalfa were more likely to be infested with Fasciola hepatica compared to those fed a mixed diet of alfalfa and crop residues (OR: 0.06, p < 0.05). These findings underscore the necessity of implementing comprehensive health programs tailored to local management and feeding conditions.